2015
DOI: 10.3389/fpls.2015.00928
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis non-specific phospholipase C1: characterization and its involvement in response to heat stress

Abstract: The Arabidopsis non-specific phospholipase C1 (NPC) protein family is encoded by the genes NPC1 – NPC6. It has been shown that NPC4 and NPC5 possess phospholipase C activity; NPC3 has lysophosphatidic acid phosphatase activity. NPC3, 4 and 5 play roles in the responses to hormones and abiotic stresses. NPC1, 2 and 6 has not been studied functionally yet. We found that Arabidopsis NPC1 expressed in Escherichia coli possesses phospholipase C activity in vitro. This protein was able to hydrolyse phosphatidylcholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 64 publications
0
45
0
Order By: Relevance
“…NPC1 protein was found in the plasma and intracellular membranes with most being associated with the intracellular membranous fraction (Figure S2c). Subcellular localization using NPC1:GFP fusion indicated that NPC1 in Arabidopsis is mostly associated with the intracellular membranes (Krčková et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…NPC1 protein was found in the plasma and intracellular membranes with most being associated with the intracellular membranous fraction (Figure S2c). Subcellular localization using NPC1:GFP fusion indicated that NPC1 in Arabidopsis is mostly associated with the intracellular membranes (Krčková et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The amino acid sequences of NPC4 and NPC5 are more closely related to one another than to NPC1. A recent study found that NPC1 from Arabidopsis hydrolyzed PC and its activity to other lipids were not tested (Krčková et al ., ). The present results indicate that NPC1 hydrolyzes both phospholipids and galactolipids.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…NPC6 hydrolyzed PC in vitro , and in vivo labelling indicates that NPC6 ‐KO reduces, but OE accelerates, PC and galactolipids turnover to TAG production in seeds. Among the six NPCs in Arabidopsis, NPC6 was unique, being associated with both the chloroplast and microsomal membrane fractions, whereas other NPCs are associated with cytosol (NPC5), the plasma membrane (NPC4), tonoplasts (NPC3) and endomembranes (NPC1 and NPC2) based on experimental data and sequence predictions (Carter et al , 2004; Peters et al , 2010; Peters et al , 2014; Krčková et al , 2015, 2017; Ngo et al , 2018). In addition, NPC6 hydrolyzes galactolipids (monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG)), and its association with chloroplasts suggests that NPC6 has the access to plastidic galactolipids to release DAG.…”
Section: Discussionmentioning
confidence: 99%
“…The Arabidopsis genome has six NPCs involved in various plant processes. NPC1 and NPC2 were involved in response to heat and P. syringae attack, respectively (Krčková et al , 2015, 2017). NPC3 and NPC4 had roles in root development and brassinolide signalling (Wimalasekera et al , 2010), and NPC4 plays a role in response to salt, abscisic acid (Peters et al , 2010), phosphate starvation (Nakamura et al , 2005; Su et al , 2018) and aluminum toxicity (Pejchar et al , 2015).…”
Section: Introductionmentioning
confidence: 99%